2014
DOI: 10.1007/s00062-013-0279-x
|View full text |Cite
|
Sign up to set email alerts
|

MR Angiography at 3 Tesla to Assess Proximal Internal Carotid Artery Stenoses: Contrast-Enhanced or 3D Time-of-Flight MR Angiography?

Abstract: Both 3D TOF-MRA and CE-MRA at 3 T are reliable tools for detecting high-grade proximal ICA stenoses (70-99 %). 3D TOF-MRA might misclassify pseudo-occlusions as complete occlusions. If there are no contraindications for CE-MRA, CE-MRA is recommended as primary MR imaging modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…These methods have undergone notable development over recent years, particularly CTA and MRA; however, despite these developments, invasive DSA remains the gold standard. [20][21][22][23][24] • The pathophysiology of carotid artery atherosclerosis is like that of other vessels.…”
Section: Other Modalities Of Carotid Artery Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods have undergone notable development over recent years, particularly CTA and MRA; however, despite these developments, invasive DSA remains the gold standard. [20][21][22][23][24] • The pathophysiology of carotid artery atherosclerosis is like that of other vessels.…”
Section: Other Modalities Of Carotid Artery Imagingmentioning
confidence: 99%
“…These methods have undergone notable development over recent years, particularly CTA and MRA; however, despite these developments, invasive DSA remains the gold standard DSA is the gold standard for comprehensive CA assessment but is not readily available. CTA can examine intra‐ and extracranial arteries simultaneously, has brevity, is good for both stroke treatment and prevention, but requires contrast and exposes to radiation. MRA is radiation‐free, but costly, requires contrast, less accurate, and is time consuming. …”
Section: Introductionmentioning
confidence: 99%
“…10 CE-MRA helps to overcome these limitations. 7,11 Several studies revealed that CE-MRA was similarly accurate to CTA for evaluating carotid stenosis but was more accurate than CDUS. [7][8][9] In most of the previous studies, radiation-induced CA and VA stenosis has been evaluated by ultrasonography and DSA in head and neck cancers, 2-4 but few studies have assessed stenosis by CE-MRA.…”
mentioning
confidence: 99%
“…Contrast enhanced 3D MRA has been shown to have high sensitivity and specificity for the determination of stenoses and occlusions of the internal carotid artery. 17,18 Accurate determination of the degree of stenosis at the carotid bifurcation and/or the internal carotid artery is crucial for treatment approach. Our study has shown that, the coronal subvolume MIP reconstruction method is more successful compared to the axial MPR and subtraction methods.…”
Section: Discussionmentioning
confidence: 99%